Impact of Marketing on Performance of Political Parties in Elections: With Special Reference to Delhi (International Journal of Innovative Research in Engineering & Management, 2021)
As one of the most competent and crucial components for the  growth of any entity, whether it is a brand, a product, or a  person, marketing is regarded to be one of the most vital  factors. The same may be said for the political world in which  we now live. Due to the rising rivalry among political parties,  they have little choice but to market them in such a way that  they can defend themselves as the greatest of all. Political  parties have been increasingly employing marketing strategies  in recent years, which has evolved into what is now known as  political marketing. Researchers will shed some insight on the  growing significance of marketing as a communication channel  for politics and political parties in this study. Despite the  availability of internet news coverage, the general population is  frequently misinformed about political topics and news that  should be covered by political marketing, and as a result, this  notion is gaining traction as it aids in analyzing voter behavior.  The goal of this study is to comprehend and demonstrate the  use of marketing as a powerful tool in the field of political  marketing in general. Although various studies have been done  on the impact of marketing during the past decade, there are  vital possibilities for more research in the future on the  marketing impacts in various fields such as healthcare, the food  industry, and many more.
Keywords: Elections; Marketing Communication; Political Parties; Political Advertising; Political Marketing